Reduction of Cr(VI) by a Consortium of Sulfate-Reducing Bacteria (SRB III) - Fude, Li (1994)
A consortium of bacteria with tolerance to high concentrations of Cr(VI) (up to 2,500 ppm) and other toxic heavy metals has been obtained from metal-refinishing wastewaters in Chengdu, People's Republic of China. This consortium consists of a range of gram-positive and gram-negative rods and has the capacity to reduce Cr(VI) to Cr(III) as amorphous precipitates which are associated with the bacterial surfaces. An endospore-producing, gram-positive rod and a gram-negative rod accumulate the most metallic precipitates, and, over time, 80 to 95% of Cr can be removed from concentrations ranging from 50 to 2,000 ppm (0.96 to 38.45 mM). Kinetic studies revealed a first-order constant for Cr removal of 0.1518 h(-1) for an initial concentration of 1,000 ppm (19.3 mM), and the sorption isothermal data could be interpreted by the Freundlich relationship. The sorption was not entirely due to a passive interaction with reactive sites on the bacterial surfaces since gamma-irradiated, killed cells could not immobilize as much metal. When U or Zn was added with the Cr, it was also removed and could even increase the total amount of Cr immobilized. The consortium was tolerant to small amounts of oxygen in the headspace of tubes, but active growth of the bacteria was a requirement for Cr immobilization through Cr(VI) reduction, resulting in the lowering of E(h). Our data suggest that the reduction was via H(2)S. This consortium has been named SRB III, and it may be useful for the bioremediation of fluid metal-refining wastes.